Anti-aging electrical epoxy resin and preparation method thereof
By introducing modified nano -nano -silicon and amino glycene in epoxy resin, the problem of traditional epoxy resin aging in high temperature, ultraviolet and humidity environment has been solved, and its mechanical performance and corrosion resistance have significantly improved, which is extended. Life life.
Patent Information
- Application Number
- CN202411960996.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Traditional epoxy resins are prone to aging in high temperature, ultraviolet rays and humid environments, resulting in a decrease in mechanical and electrical properties and a shorter service life.
By introducing modified nano -nanocriles and amino glycene, epoxy resin matrix has been significantly improved in terms of anti -aging and corrosion resistance. Nano -sanxia is modified by a sirriomide coupling agent to improve its decentralization and compatibility in epoxy resin; amino glycene is treated with aminoization, which enhances its binding force with the interface of epoxy resin.
It significantly improves the mechanical performance, aging resistance and corrosion resistance of epoxy resin, extended the service life of the material, and reduced the consumption of antioxidants and ultraviolet absorbers.
Smart Images

Figure CN119371778A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrical epoxy resin materials, and in particular relates to an anti-aging electrical epoxy resin and a preparation method thereof. Background Art
[0002] Anti-aging electrical epoxy resins are widely used in the fields of electronics, electrical and high-voltage insulation. They are mainly used to manufacture electronic packaging materials, electrical insulation materials and coatings to protect electronic components from damage by environmental factors and increase the service life of equipment. Epoxy resins have excellent mechanical properties, chemical resistance, good electrical insulation and bonding properties, so they are widely used in electronic and electrical equipment. However, the disadvantages of epoxy resins are that they are brittle, have poor impact resistance, and are prone to aging when exposed to high temperature, ultraviolet rays and humid environments for a long time. These problems will affect their durability and stability in electrical applications. Traditional epoxy resins are prone to thermal degradation at high temperatures, resulting in decreased mechanical and electrical properties; ultraviolet rays and moisture can cause chemical aging of epoxy resins, causing them to lose their original properties; under long-term stress, epoxy resins are prone to fatigue cracks, affecting their service life; under the action of oxygen and free radicals, epoxy resins will undergo oxidative degradation, resulting in material performance degradation; certain chemicals (such as acids, alkalis, and solvents) will corrode epoxy resins, affecting their long-term stability. In addition, the aging of epoxy resin mainly includes two forms: physical aging and chemical aging. Physical aging is mainly manifested as brittleness, cracking and degradation of mechanical properties of the material. This is usually due to the influence of factors such as temperature changes and stress on the material during use; chemical aging is mainly manifested as degradation of the material, reduced crosslinking density and performance degradation. This is usually due to the erosion of environmental factors such as oxygen, ultraviolet rays and moisture during the use of the material. After aging, the mechanical strength, electrical properties and corrosion resistance of the resin will decrease significantly, which may easily lead to problems such as insulation failure in the equipment, thus seriously affecting the safety and service life of the system. Therefore, based on the above problems, it is extremely necessary to develop an electrical epoxy resin that can effectively resist aging and corrosion. Summary of the invention
[0003] In view of the defects of the prior art, the object of the present invention is to provide an anti-aging electrical epoxy resin and a preparation method thereof.
[0004] The technical effect described in the present invention is achieved through the following technical scheme: an anti-aging electrical epoxy resin, which is composed of the following raw materials in parts by weight: 70 to 80 parts of epoxy resin, 3 to 5 parts of modified nano-silicon dioxide, 1 to 3 parts of amino graphene, 5 to 8 parts of polyurethane, 0.5 to 1 part of methyltriethoxysilane, 0.1 to 0.5 parts of sodium dodecyl sulfate, 0.5 to 1 part of antioxidant and 0.5 to 1 part of ultraviolet absorber.
[0005] Preferably, the epoxy resin is bisphenol A type epoxy resin.
[0006] Preferably, the antioxidant is any one of 2,6-di-tert-butyl-p-cresol, ascorbic acid, N-phenyl-α-naphthylamine and dilauryl thiodipropionate.
[0007] Preferably, the ultraviolet absorber is any one of 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, benzyl salicylate and phenyl salicylic acid.
[0008] Preferably, the specific preparation steps of the modified nano-silicon dioxide are as follows: A1: Add nano-silica to anhydrous ethanol, and perform ultrasonic dispersion treatment at 100-200W for 30-60min to obtain a nano-silica dispersion; add γ-glycidyloxypropyltrimethoxysilane to anhydrous ethanol, stir and mix evenly, then slowly drop deionized water and acetic acid, and stir and react at 200-300rpm for 10-30min to obtain a coupling agent solution; A2: slowly adding the coupling agent solution prepared in step A1 to the nano-silica dispersion prepared in step A1, stirring at 300-500 rpm for 12 hours at room temperature, centrifuging, repeatedly washing with deionized water for 5 times, and vacuum drying at 60-80° C. for 12-24 hours to obtain modified nano-silica; Preferably, in step A1, the ratio of the amount of the nano-silicon dioxide to anhydrous ethanol is 1 g: 40-50 mL; the ratio of the amount of γ-glycidyloxypropyltrimethoxysilane, anhydrous ethanol, deionized water and acetic acid is 1 g: 15-20 mL: 0.5-0.6 mL: 0.04-0.05 mL; Preferably, in step A2, the volume ratio of the coupling agent solution to the nano-silicon dioxide dispersion is 0.02-0.03:1.
[0009] Preferably, the specific preparation steps of the amination graphene are as follows: B1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the temperature at 0-5°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add potassium permanganate. After the addition is complete, raise the temperature to 35-40°C, stir and react for 12-24 hours, slowly add deionized water to dilute, then add hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution for 3 times, and vacuum dry at 60°C for 12-24 hours to obtain graphene oxide; B2: Disperse the graphene oxide prepared in step B1 in dimethyl sulfoxide, and perform ultrasonic dispersion treatment at 100-150W for 30-60min to obtain a graphene oxide dispersion; control the temperature at 0-5°C, slowly drop 3-aminopropyltriethoxysilane into the graphene oxide dispersion, and after the dropwise addition is completed, raise the temperature to 60°C, continue stirring for 12-24h, centrifuge, repeatedly wash with deionized water and ethanol for 3 times, and vacuum dry at 60°C for 12-24h to obtain amino graphene; Preferably, in step B1, the ratio of the amount of graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:2-3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-4mL:1g; Preferably, in step B2, the ratio of the graphene oxide, dimethyl sulfoxide and 3-aminopropyltriethoxysilane is 3-5 mg:1 mL:0.04-0.05 mL.
[0010] Preferably, another aspect of the present invention is to provide a method for preparing an anti-aging electrical epoxy resin, and the specific preparation steps are as follows: S1: adding modified nano-silica and amino graphene to epoxy resin in proportion by weight, stirring at 1000-1500 rpm for 40-60 min, adding sodium dodecyl sulfate after being evenly dispersed, stirring at 800-1200 rpm for 15-30 min, then adding polyurethane, antioxidant and ultraviolet absorber, stirring at 500-800 rpm for 15-30 min, and obtaining a mixed raw material; S2: curing the mixed raw material prepared in step S1 at 80° C. for 2 h, and then curing at 120° C. for 2 h to obtain a cured material; adding methyltriethoxysilane to 100 parts by weight of anhydrous ethanol, adding deionized water of one-half part by weight of the substrate, stirring at 300-500 rpm for 15-30 min to obtain a hydrolyzed solution; S3: spraying the hydrolysis solution prepared in step S2 onto the surface of the curing material prepared in step S2, and after spraying, vacuum drying at 60-80° C. for 1-2 hours to obtain epoxy resin; Preferably, in step S3, the spraying operation parameters are 0.1-0.3 MPa, a distance of 15-20 cm, a speed of 20-30 cm / s, and a standing time of 5-10 minutes after each spraying, for a total of 3 sprayings.
[0011] The beneficial effects of the present invention are as follows: The present invention significantly improves the anti-aging and corrosion resistance of the epoxy resin matrix by introducing silane-modified nano-silica and amino-modified graphene. Nano-silica is easily agglomerated in the epoxy resin matrix due to its high specific surface area and surface energy, resulting in uneven dispersion; the surface of the nano-silica is modified by a silane coupling agent (γ-glycidyloxypropyltrimethoxysilane), and organic functional groups such as epoxy groups are introduced on the surface of the nano-silica, so that the surface is changed from hydrophilic to organic, and its dispersibility and compatibility in the epoxy resin are significantly improved. One end (siloxane group) of the silane coupling agent generates silanol after hydrolysis, and undergoes a dehydration condensation reaction with the hydroxyl group on the surface of the nano-silica to form a stable Si-O-Si covalent bond; the epoxy group at the other end can react with the active group in the epoxy resin matrix to further achieve cross-linking. Through this dual-functional structure, nano-silica can not only be firmly bonded to the matrix, but also significantly enhance the interfacial bonding force between the filler and the matrix, reduce interface defects and stress concentration, and thus improve the mechanical properties and aging resistance of the epoxy resin.
[0012] The present invention makes the graphene surface more affinity with epoxy resin through amination modification, and the amino group can react chemically with the epoxy group to form a stable covalent bond, thereby improving the dispersibility and compatibility of graphene in epoxy resin, enhancing the interfacial bonding force, reducing interfacial defects, and improving the stress transfer efficiency. In addition, the high thermal conductivity and electrical conductivity of graphene itself can form an effective heat conduction network in the matrix, significantly improving the heat dissipation performance of the material and preventing material aging caused by high temperature. At the same time, the lamellar structure of graphene can form a physical barrier to delay the penetration of oxygen, moisture and corrosive media, and amination further enhances the barrier effect, so that the material has a longer service life in a corrosive environment. Silane-modified nano-silica and amination-modified graphene are evenly dispersed in the epoxy resin matrix to form multiple physical barriers to synergistically slow down the penetration of aging factors and corrosive media. Nano-silica enhances the hardness and rigidity of the material, while amination of graphene improves its toughness and thermal conductivity. The synergistic effect of the two makes the material have high strength, high toughness and excellent thermal stability, further enhancing the durability of the material in electrical application environments. At the same time, these added auxiliary materials effectively reduce the penetration of oxygen and ultraviolet rays, slowing down the consumption rate of antioxidants and ultraviolet absorbers, making their chemical protection inside the material more durable. Modified nano-silica forms a strong chemical bond with the matrix through the silane coupling agent, while amination of graphene forms additional hydrogen bonds with the matrix and nano-silica through the amino group. The multiple interface bonding mechanisms significantly improve the compatibility between the nano-filler and the matrix and reduce interface defects.
[0013] The present invention adopts methyltriethoxysilane (MTES) hydrophobic treatment on the material surface, and the silanol groups generated by hydrolysis form Si-O-Si bonds with each other, and self-assemble to form a uniform hydrophobic coating; the unreacted silanol groups of the MTES coating can form a compatible interface with the glycidyl ether groups of modified nano-silicon dioxide, and the amino groups of amination graphene can also react with the silanol groups in the coating to form stable chemical bonds, so as to achieve a good combination between the three, so that the dispersibility and compatibility of the filler in the matrix are further improved, and the material performance caused by the poor interface is effectively avoided. This silane-based hydrophobic coating can not only effectively delay the penetration of moisture and corrosive media, but also adhere to the epoxy resin surface by physical adsorption and hydrogen bonding, further improving the weather resistance and moisture resistance of the overall material. The hydrophobic treatment of the outer layer blocks the entry of moisture and corrosive substances, and the nano filler of the inner layer further slows down the diffusion of the residual penetrant, and the joint action of the inner and outer layers significantly improves the corrosion resistance of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 It is a graph showing changes in tensile strength of epoxy resins prepared in Example 2 of the present invention and Comparative Examples 1 to 4 under ultraviolet aging tests; Figure 2 It is a thermal deformation temperature diagram of the epoxy resin prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 3 It is a graph showing the change in tensile strength of the epoxy resins prepared in Example 2 of the present invention and Comparative Examples 1 to 4 under corrosion resistance tests. DETAILED DESCRIPTION
[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.
[0017] Example 1: An anti-aging electrical epoxy resin, comprising the following raw materials in parts by weight: 70 parts of epoxy resin, 3 parts of modified nano-silica, 1 part of amino graphene, 5 parts of polyurethane, 0.5 parts of methyltriethoxysilane, 0.1 parts of sodium dodecyl sulfate, 0.5 parts of antioxidant and 0.5 parts of ultraviolet absorber.
[0018] The specific preparation steps of modified nano-silica are as follows: A1: Add 10g of nano-silica to 400mL of anhydrous ethanol, and perform ultrasonic dispersion treatment at 100W for 60min to obtain a nano-silica dispersion; add 10g of γ-glycidyloxypropyltrimethoxysilane to 150mL of anhydrous ethanol, stir and mix evenly, then slowly drop 5mL of deionized water and 0.4mL of acetic acid, and stir and react at 200rpm for 30min to obtain a coupling agent solution; A2: Slowly add 16 mL of the coupling agent solution prepared in step A1 to 400 mL of the nano-silica dispersion prepared in step A1, stir at 300 rpm for 12 h at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 60°C for 24 h to obtain modified nano-silica; The specific preparation steps of amination graphene are as follows: B1: Add 10g of graphite powder to a flask, slowly add 200mL of concentrated sulfuric acid and 20mL of concentrated phosphoric acid, control the temperature at 5°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add 30g of potassium permanganate. After the addition is complete, raise the temperature to 35°C, stir and react for 24h, slowly add 800mL of deionized water to dilute, then add 30mL of hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution 3 times, and vacuum dry at 60°C for 12h to obtain graphene oxide; B2: 900 mg of graphene oxide prepared in step B1 was dispersed in 300 mL of dimethyl sulfoxide, and subjected to 100 W ultrasonic dispersion treatment for 60 min to obtain a graphene oxide dispersion; the temperature was controlled at 5°C, and 12 mL of 3-aminopropyltriethoxysilane was slowly added to the graphene oxide dispersion. After the addition was completed, the temperature was raised to 60°C, and the mixture was stirred for 12 h, centrifuged, and washed with deionized water and ethanol for 3 times, and vacuum dried at 60°C for 12 h to obtain amino graphene; The specific preparation steps of anti-aging electrical epoxy resin are as follows: S1: adding modified nano-silica and amino graphene to bisphenol A epoxy resin in proportion by weight, stirring at 1000 rpm for 60 min, adding sodium dodecyl sulfate after being evenly dispersed, stirring at 800 rpm for 30 min, then adding polyurethane, 2,6-di-tert-butyl-p-cresol and 2-hydroxy-4-methoxybenzophenone, stirring at 500 rpm for 30 min, to obtain a mixed raw material; S2: curing the mixed raw material prepared in step S1 at 80° C. for 2 h, and then curing at 120° C. for 2 h to obtain a cured material; adding methyltriethoxysilane to 100 parts by weight of anhydrous ethanol, adding deionized water of one-half part by weight of the substrate, stirring at 300 rpm for 30 min to obtain a hydrolyzed solution; S3: Spray the hydrolysis solution prepared in step S2 onto the surface of the curing material prepared in step S2, the spraying operation parameters are 0.1MPa, distance 15cm, speed 20cm / s, stand for 5min after each spraying, spray 3 times in total, after spraying, vacuum dry at 60°C for 2h to obtain epoxy resin.
[0019] Example 2: An anti-aging electrical epoxy resin, comprising the following raw materials in parts by weight: 80 parts of epoxy resin, 5 parts of modified nano-silica, 3 parts of amino graphene, 8 parts of polyurethane, 1 part of methyltriethoxysilane, 0.5 parts of sodium dodecyl sulfate, 1 part of antioxidant and 1 part of ultraviolet absorber.
[0020] The specific preparation steps of modified nano-silica are as follows: A1: Add 10g of nano-silica to 500mL of anhydrous ethanol, and perform ultrasonic dispersion treatment at 200W for 40min to obtain a nano-silica dispersion; add 10g of γ-glycidyloxypropyltrimethoxysilane to 200mL of anhydrous ethanol, stir and mix evenly, then slowly drop 6mL of deionized water and 0.5mL of acetic acid, and stir and react at 300rpm for 20min to obtain a coupling agent solution; A2: Slowly add 25 mL of the coupling agent solution prepared in step A1 to 500 mL of the nano-silica dispersion prepared in step A1, stir at 500 rpm for 12 h at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 80°C for 18 h to obtain modified nano-silica; The specific preparation steps of amination graphene are as follows: B1: Add 10g of graphite powder to a flask, slowly add 250mL of concentrated sulfuric acid and 30mL of concentrated phosphoric acid, control the temperature at 4°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add 30g of potassium permanganate. After the addition is complete, raise the temperature to 40°C, stir and react for 18h, slowly add 1000mL of deionized water to dilute, then add 40mL of hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution 3 times, and vacuum dry at 60°C for 24h to obtain graphene oxide; B2: Disperse 1500 mg of graphene oxide prepared in step B1 in 300 mL of dimethyl sulfoxide, and perform ultrasonic dispersion treatment at 150 W for 50 min to obtain a graphene oxide dispersion; control the temperature at 4°C, slowly drop 15 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, and after the dropwise addition is completed, raise the temperature to 60°C, continue stirring for 24 h, centrifuge, repeat washing with deionized water and ethanol for 3 times, and vacuum dry at 60°C for 24 h to obtain amino graphene; The specific preparation steps of anti-aging electrical epoxy resin are as follows: S1: adding modified nano-silica and amino-modified graphene to bisphenol A epoxy resin in proportion by weight, stirring at 1500 rpm for 50 min, adding sodium dodecyl sulfate after being evenly dispersed, stirring at 1200 rpm for 20 min, then adding polyurethane, dilauryl thiodipropionate and 2,2'-dihydroxy-4-methoxybenzophenone, stirring at 800 rpm for 20 min, to obtain a mixed raw material; S2: curing the mixed raw material prepared in step S1 at 80° C. for 2 h, and then curing at 120° C. for 2 h to obtain a cured material; adding methyltriethoxysilane to 100 parts by weight of anhydrous ethanol, adding deionized water of one-half part by weight of the substrate, stirring at 500 rpm for 20 min to obtain a hydrolyzed solution; S3: Spray the hydrolysis solution prepared in step S2 onto the surface of the curing material prepared in step S2, the spraying operation parameters are 0.3MPa, distance 20cm, speed 25cm / s, stand for 10min after each spraying, spray 3 times in total, after spraying, vacuum dry at 80°C for 1.5h to obtain epoxy resin.
[0021] Example 3: An anti-aging electrical epoxy resin, comprising the following raw materials in parts by weight: 75 parts of epoxy resin, 4 parts of modified nano-silica, 2 parts of amino graphene, 7 parts of polyurethane, 0.8 parts of methyltriethoxysilane, 0.3 parts of sodium dodecyl sulfate, 0.8 parts of antioxidant and 0.8 parts of ultraviolet absorber.
[0022] The specific preparation steps of modified nano-silica are as follows: A1: Add 10g of nano-silica to 450mL of anhydrous ethanol, and perform ultrasonic dispersion treatment at 150W for 30min to obtain a nano-silica dispersion; add 10g of γ-glycidyloxypropyltrimethoxysilane to 180mL of anhydrous ethanol, stir and mix evenly, then slowly dropwise add 5.5mL of deionized water and 0.45mL of acetic acid, and stir and react at 250rpm for 10min to obtain a coupling agent solution; A2: Slowly add 20 mL of the coupling agent solution prepared in step A1 to 450 mL of the nano-silica dispersion prepared in step A1, stir at 400 rpm for 12 h at room temperature, centrifuge, wash with deionized water 5 times, and vacuum dry at 70°C for 12 h to obtain modified nano-silica; The specific preparation steps of amination graphene are as follows: B1: Add 10g of graphite powder to a flask, slowly add 240mL of concentrated sulfuric acid and 25mL of concentrated phosphoric acid, control the temperature to 0℃, stir and disperse evenly, raise the temperature to 10℃, and then slowly add 30g of potassium permanganate. After the addition is complete, raise the temperature to 38℃, stir and react for 12h, slowly add 900mL of deionized water to dilute, then add 35mL of hydrogen peroxide, centrifuge, repeat washing with deionized water and 1M HCl solution 3 times, and vacuum dry at 60℃ for 18h to obtain graphene oxide; B2: Disperse 1200 mg of graphene oxide prepared in step B1 in 300 mL of dimethyl sulfoxide, and perform ultrasonic dispersion treatment at 140 W for 30 min to obtain a graphene oxide dispersion; control the temperature to 0°C, slowly drop 14 mL of 3-aminopropyltriethoxysilane into the graphene oxide dispersion, and after the dropwise addition is completed, raise the temperature to 60°C, continue stirring for 18 h, centrifuge, repeat washing with deionized water and ethanol for 3 times, and vacuum dry at 60°C for 18 h to obtain amino graphene; The specific preparation steps of anti-aging electrical epoxy resin are as follows: S1: adding modified nano-silica and amino graphene to bisphenol A epoxy resin in proportion by weight, stirring at 1400 rpm for 40 min, adding sodium dodecyl sulfate after being evenly dispersed, stirring at 1000 rpm for 15 min, then adding polyurethane, N-phenyl-α-naphthylamine and benzyl salicylate, stirring at 700 rpm for 15 min, to obtain a mixed raw material; S2: curing the mixed raw material prepared in step S1 at 80° C. for 2 h, and then curing at 120° C. for 2 h to obtain a cured material; adding methyltriethoxysilane to 100 parts by weight of anhydrous ethanol, adding deionized water of one-half part by weight of the substrate, stirring at 400 rpm for 15 min to obtain a hydrolyzed solution; S3: Spray the hydrolysis solution prepared in step S2 onto the surface of the curing material prepared in step S2, the spraying operation parameters are 0.2MPa, distance 18cm, speed 30cm / s, stand for 8min after each spraying, spray 3 times in total, after spraying, vacuum dry at 70°C for 1h to obtain epoxy resin.
[0023] Comparative Example 1: The operation of Comparative Example 1 is basically the same as that of Example 2, except that no modified nano-silica is added in Comparative Example 1.
[0024] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that amino-treated graphene is not used in Comparative Example 2.
[0025] Comparative Example 3: The operation of Comparative Example 3 is substantially the same as that of Example 2, except that no methyltriethoxysilane hydrophobic treatment is used in Comparative Example 3.
[0026] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that in Comparative Example 4, nano-silica is used to replace modified nano-silica.
[0027] Performance Testing: Mechanical strength and insulation test: The tensile strength, flexural strength and compressive strength tests were performed on the epoxy resin material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 using a universal material testing machine. The results are shown in Table 1 below. The insulation resistivity of the epoxy resin material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 was tested in accordance with GB / T1409-2006. The results are shown in Table 1 below.
[0028] Table 1. Mechanical strength and insulation test results of epoxy resin materials
[0029] It can be seen from the results in Table 1 that the epoxy resin material prepared by the present invention has excellent mechanical properties and insulation. At the same time, the addition of amino graphene has no significant effect on the insulation of the epoxy resin material; from the results of Comparative Example 1 and Example 2, it can be seen that nano-silicon dioxide can significantly enhance the hardness, rigidity and anti-aging properties of the material due to its high specific surface area and surface energy. The lack of modified nano-silicon dioxide leads to a significant decrease in the hardness and rigidity of the material; from the results of Comparative Example 2 and Example 2, it can be seen that the addition of amino graphene can improve the toughness and impact resistance of the material. Not using amino graphene may lead to increased brittleness of the material, reduced stress transfer efficiency, and a significant decrease in mechanical strength; from the results of Comparative Example 4 and Example 2, it can be seen that the lack of silane-modified nano-silicon dioxide may lead to poor dispersibility of nano-silicon dioxide and agglomeration, thereby affecting the tensile strength and compressive strength of the matrix.
[0030] UV aging test: The epoxy resin material samples prepared in Example 2 and Comparative Examples 1 to 4 were subjected to UV lamp aging test, and the test parameters were UVA-340 lamp tube simulating ultraviolet rays (0.35 W / m 2 ), temperature 60℃, humidity 55%, photoperiod of 12h light, 12h dark, 500h test, record the surface condition changes of the samples at 96h, 240h and 500h, the results are shown in Table 2 below, as well as the percentage change in tensile strength (tensile strength change = (tensile strength before test - tensile strength after test) / tensile strength before test × 100%), the results are shown in Table 2 below Figure 1 shown.
[0031] Table 2. Results of surface condition changes in UV aging tests of epoxy resin materials
[0032] From Table 2 and Figure 1 As a result, it can be seen that the epoxy resin material prepared by the present invention has excellent anti-aging performance and can be effectively used for a long time; from the results of Comparative Example 1 and Example 2, it can be seen that due to the lack of filler effect of modified nano-silicon dioxide, the hardness and rigidity of the material cannot be effectively enhanced. At the same time, the lack of nano-silicon dioxide makes the material more susceptible to molecular chain breakage under ultraviolet irradiation, resulting in accelerated aging and obvious decline in mechanical properties; from the results of Comparative Example 2 and Example 2, it can be seen that the high thermal conductivity of graphene itself helps to disperse heat and reduce stress concentration in local high-temperature areas, thereby slowing down the aging of the material caused by temperature changes or ultraviolet irradiation, while the material lacking amino-modified graphene cannot form an effective heat conduction network. This may lead to the aggravation of the aging process in the temperature concentration area, resulting in obvious cracking and a significant decrease in the mechanical properties of the material; from the results of Comparative Example 3 and Example 2, it can be seen that due to the lack of hydrophobic treatment, this may cause moisture accumulation on the surface of the material, and the presence of moisture will accelerate the degradation reaction caused by ultraviolet rays, resulting in obvious cracking and yellowing on the surface, as well as a significant decrease in the mechanical properties of the material; from the results of Comparative Example 4 and Example 2, it can be seen that the surface of nano-silica lacks organic functional groups, has strong hydrophilicity, and is easy to agglomerate in the epoxy resin, which may lead to its uneven dispersion, thereby affecting its reinforcement effect, and then causing the material's anti-aging performance under ultraviolet irradiation to be significantly decreased.
[0033] Thermal performance test: The epoxy resin materials prepared in Example 2 and Comparative Examples 1 to 4 were subjected to heat deformation temperature tests. The deformation temperatures of the samples were tested at 0.45 MPa and 1.8 MPa at a heating rate of 120°C / h. The control group was bisphenol A epoxy resin. The results are as follows: Figure 2 shown.
[0034] Depend on Figure 2 As a result, it can be seen that the epoxy resin material prepared by the present invention has an extremely high heat deformation temperature through the synergistic effect of multiple substances; from the results of Comparative Example 1 and Example 2, it can be seen that due to the lack of modified nano-silica, filler aggregation may exist in the epoxy resin, which will lead to poor dispersibility and compatibility of the material, and its thermal performance may be poor, thereby leading to a lower heat deformation temperature; from the results of Comparative Example 2 and Example 2, it can be seen that the lack of amino graphene may reduce the thermal conductivity and interfacial bonding of the material, affect the transmission of thermal stress, and cause the heat deformation temperature to be significantly affected; from the results of Comparative Example 3 and Example 2, it can be seen that the hydrophobic treatment improves the water resistance and corrosion resistance of the material surface, prevents the erosion of the material by moisture and corrosive media, thereby indirectly improving the thermal performance. The lack of this treatment may cause the material to be damaged in a humid environment, affecting its thermal stability and deformation temperature to a certain extent; from the results of Comparative Example 4 and Example 2, it can be seen that unmodified nano-silica is usually poorly dispersible in epoxy resin, and its hydrophilicity leads to weak bonding between the filler and the resin matrix, which may lead to a lower heat deformation temperature.
[0035] Corrosion resistance test: Use 5% NaCl solution to continuously spray the epoxy resin material samples prepared in Example 2 and Comparative Examples 1 to 4 at 35°C for 16 hours, then stop for 8 hours, and test for 96 hours. The percentage change in tensile strength at 24 hours, 48 hours and 96 hours (tensile strength change = (tensile strength before test - tensile strength after test) / tensile strength before tensile × 100%) is as follows: Figure 3 shown.
[0036] Depend on Figure 3As a result, the epoxy resin material prepared by the present invention has excellent corrosion resistance. As can be seen from the results of Comparative Example 1 and Example 2, due to the lack of modified nano-silicon dioxide, there is a lack of effective interface bonding force and filler reinforcement, which may lead to low hardness and rigidity of the material, and then cause it to deform and age in a corrosive environment, resulting in a significant impact on the tensile strength. As can be seen from the results of Comparative Example 2 and Example 2, the lack of amino-modified graphene will lead to a decrease in the penetration resistance of corrosive media. The lack of graphene makes it impossible for the material to effectively dissipate heat through the heat conduction network, and there is also a lack of physical barrier protection, resulting in poor corrosion resistance of the material. The tensile strength is significantly affected; from the results of Comparative Example 3 and Example 2, it can be seen that the hydrophobic coating can effectively prevent the intrusion of moisture, and enhance the weather resistance and moisture resistance of the material through physical adsorption and hydrogen bonding. The lack of a hydrophobic coating makes the material more susceptible to damage from the external environment, especially in a humid environment, which causes the corrosion rate of the material to accelerate, thereby affecting the tensile strength; from the results of Comparative Example 4 and Example 2, it can be seen that since there is no epoxy group on the surface of the nano-silica, it cannot undergo an effective chemical reaction with the epoxy resin matrix, resulting in weak interfacial bonding, which in turn affects the tensile strength of the material in a corrosive environment.
[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-aging electrical epoxy resin, characterized in that: The composition includes the following raw materials in parts by weight: 70-80 parts of epoxy resin, 3-5 parts of modified nano silicon dioxide, 1-3 parts of amino graphene, 5-8 parts of polyurethane, 0.5-1 parts of methyl triethoxy silane, 0.1-0.5 parts of sodium dodecyl sulfate, 0.5-1 parts of antioxidant and 0.5-1 parts of ultraviolet absorber; The specific preparation steps of the modified nano silicon dioxide are as follows: A1: Add nano-silica to anhydrous ethanol, perform ultrasonic dispersion treatment, and obtain a nano-silica dispersion; add γ-glycidyloxypropyltrimethoxysilane to anhydrous ethanol, stir and mix evenly, then slowly drop deionized water and acetic acid, stir and react, and obtain a coupling agent solution; A2: Slowly add the coupling agent solution prepared in step A1 to the nano-silica dispersion prepared in step A1, stir and react at room temperature, centrifuge, repeatedly wash with deionized water, and vacuum dry to obtain modified nano-silica.
2. An anti-aging electrical epoxy resin according to claim 1, characterized in that: The specific preparation steps of the amino graphene are as follows: B1: Add graphite powder to a flask, slowly add concentrated sulfuric acid and concentrated phosphoric acid, control the temperature at 0-5°C, stir and disperse evenly, raise the temperature to 10°C, and then slowly add potassium permanganate. After the addition is complete, raise the temperature, stir to react, slowly add deionized water to dilute, then add hydrogen peroxide, centrifuge, repeatedly wash with deionized water and 1M HCl solution, and vacuum dry to obtain graphene oxide; B2: Disperse the graphene oxide prepared in step B1 in dimethyl sulfoxide, and perform ultrasonic dispersion treatment to obtain a graphene oxide dispersion; control the temperature at 0-5°C, and slowly drop 3-aminopropyltriethoxysilane into the graphene oxide dispersion. After the dropwise addition is completed, increase the temperature to 60°C, continue stirring, centrifuge, repeatedly wash with deionized water and ethanol, and vacuum dry to obtain amino graphene.
3. An anti-aging electrical epoxy resin according to claim 2, characterized in that: The antioxidant is any one of 2,6-di-tert-butyl-p-cresol, ascorbic acid, N-phenyl-α-naphthylamine and dilauryl thiodipropionate.
4. An anti-aging electrical epoxy resin according to claim 3, characterized in that: The ultraviolet absorber is any one of 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, benzyl salicylate and phenyl salicylic acid.
5. The anti-aging electrical epoxy resin according to claim 4, characterized in that: In step A1, the ratio of the amount of the nano-silica to anhydrous ethanol is 1 g: 40-50 mL; the ratio of the amount of γ-glycidyloxypropyltrimethoxysilane, anhydrous ethanol, deionized water and acetic acid is 1 g: 15-20 mL: 0.5-0.6 mL: 0.04-0.05 mL.
6. The anti-aging electrical epoxy resin according to claim 5, characterized in that: In step A2, the volume ratio of the coupling agent solution to the nano-silicon dioxide dispersion is 0.02-0.03:
1.
7. An anti-aging electrical epoxy resin according to claim 6, characterized in that: In step B1, the ratio of the amount of graphite powder, concentrated sulfuric acid and concentrated phosphoric acid is 1g:20-25mL:2-3mL; the ratio of the amount of potassium permanganate, deionized water, hydrogen peroxide and graphite powder is 3g:80-100mL:3-4mL:1g.
8. An anti-aging electrical epoxy resin according to claim 7, characterized in that: In step B2, the ratio of the amount of graphene oxide, dimethyl sulfoxide and 3-aminopropyltriethoxysilane is 3-5 mg:1 mL:0.04-0.05 mL.
9. A method for preparing an anti-aging electrical epoxy resin according to any one of claims 1 to 8, characterized in that: The specific preparation steps are as follows: S1: adding modified nano-silica and amino graphene to epoxy resin in proportion by weight, stirring, and after uniform dispersion, adding sodium dodecyl sulfate, stirring, and then adding polyurethane, antioxidant and ultraviolet absorber, stirring to obtain a mixed raw material; S2: curing the mixed raw material prepared in step S1 at 80° C. for 2 h, and then curing at 120° C. for 2 h to obtain a cured material; adding methyltriethoxysilane to anhydrous ethanol, adding deionized water in an amount of one-half the weight of the substrate, stirring to react, and obtaining a hydrolysis solution; S3: spraying the hydrolysis solution prepared in step S2 onto the surface of the curing material prepared in step S2, and after spraying, vacuum drying to obtain epoxy resin.
10. A method for preparing the anti-aging electrical epoxy resin according to claim 9, characterized in that: In step S3, the spraying operation parameters are 0.1-0.3 MPa, a distance of 15-20 cm, a speed of 20-30 cm / s, and a standing time of 5-10 minutes after each spraying, for a total of 3 sprayings.
Citation Information
Patent Citations
Graphene / nano-silica / epoxy resin composite material and preparation method thereof
CN107459774A
Graphene oxide-based waterproof insulating adhesive
CN109294501A
Preparation method of nano-silica modified graphene oxide / epoxy resin composite material
CN111763405A
Composite anticorrosive material containing modified graphene oxide and preparation method thereof
CN114958151A
Cited By
Composite layered protection paste for folding screen and production process of composite layered protection paste
CN120134770A
Novel waterproof building material and preparation method thereof
CN120137352A
Electronic-grade epoxy resin composition and preparation method thereof
CN120209497A
Composite material for electrical fence and preparation method thereof
CN120209512A
A composite material for an electric fence and a method of making the same
CN120209512B